Trends in antimicrobial resistance of fecal shigella and Salmonella isolates in Tehran, Iran - Ashtiani Mohammad; Monajemzadeh Maryam; Kashi Leila (Wolters Kluwer Medknow Publications, 2009)
Context: The resistance of bacteria to commonly prescribed antibiotics is increasing both in developing as well as developed countries. Resistance has emerged even to newer, more potent antimicrobial agents. The present study was therefore undertaken to report resistance rates to antimicrobial agents in 2487 stool culture isolates in a tertiary care hospital between 1996 and 2000 and 2001 and 2005. Materials and Methods: During 1996 to 2005, 31776 fecal samples were collected from all patients having diarrhea aged> 1 month to 14 years old. Microbiology records were reviewed and information on each isolate regarding its antimicrobial susceptibility profile was collected and recorded. Statistical Analysis Used: The statistical analysis was performed using SPSS, Version 11.5 software. Results: Of the positive fecal cultures, 1329 (53.43%) of the isolates were Shigella spp and 700 (28.14%) of the isolates were Salmonella spp. Resistance to antimicrobial agents increased among most of the pathogens between 2001 and 2005. An increase in the rate of resistance was observed in Shigella spp for kanamycin (from 11 to 37%) and ceftazidime (from 1 to 9.9%) and among Salmonella spp. for nalidixic acid (from 9.2 to 42.3%) and ceftazidime (from 3 to 23.4%). Conclusions: Routine surveillance of antimicrobial susceptibilities to all classes of clinically used agents is necessary to detect resistance trends in different parts of world, detecting the emergence of new resistance mechanisms that guide infection control measures and public health guidelines; such trends may help in identifying outbreaks of resistant organisms. Such a check seems to be the best way to find appropriate antibiotic regimens